5x-12=4x+3

Simple and best practice solution for 5x-12=4x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-12=4x+3 equation:


Simplifying
5x + -12 = 4x + 3

Reorder the terms:
-12 + 5x = 4x + 3

Reorder the terms:
-12 + 5x = 3 + 4x

Solving
-12 + 5x = 3 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-12 + 5x + -4x = 3 + 4x + -4x

Combine like terms: 5x + -4x = 1x
-12 + 1x = 3 + 4x + -4x

Combine like terms: 4x + -4x = 0
-12 + 1x = 3 + 0
-12 + 1x = 3

Add '12' to each side of the equation.
-12 + 12 + 1x = 3 + 12

Combine like terms: -12 + 12 = 0
0 + 1x = 3 + 12
1x = 3 + 12

Combine like terms: 3 + 12 = 15
1x = 15

Divide each side by '1'.
x = 15

Simplifying
x = 15

See similar equations:

| 5x+3=413 | | 8-u=7u | | 66366737373773737373+6636673772727= | | -3+(5+x)=80 | | w=5+3(x-1) | | 11(2m+2)-6=4(3m-2) | | 5+3y=8x | | 4p-7=3(p-5) | | 5x+10y=230 | | 3x+36=13x-7 | | 85+120+101+3x-6+x=360 | | 2x(x^2-25)=0 | | 3.99d=1.99d+50 | | 5x-3=142 | | -2x-2-3=-3 | | x+2=14-2x | | (5+a)-(9+b)=-4+(a-b) | | -56+3x=-5x+48 | | 18=-12+6 | | sec^2x+4tanx=0 | | 9t^2-51t+30=0 | | 9x-12=48 | | 45=15-(m-10) | | x+6=2y-4 | | 3xy+3x-2xy= | | 9(a^2-4)+1=0 | | 7(47)-5y=34 | | 4+x=9-2 | | 100a^2-500a+600= | | 4x(x-3)+5x=48 | | 100a^2-500a-600= | | -4(2-y)+3y=(y-4) |

Equations solver categories